An evaluation of the adequacy of the existing framework for source-based taxation in South Africa as applied to the new business models proliferated by the digitalisation of the economy - Roche, James (Department of Commercial Law, 2022)
The advent of digitalisation has fundamentally shifted the manner in which the commercial world carries on business away from the traditionally established brick-and-mortar business models. The thorough permeation of digitalisation through the economy has resulted in the proliferation of new digitalised business models. Resultingly, there is growing concern that economic actors are increasingly able to avoid, remove or significantly reduce their tax liability within the existent framework which was conceived in light of traditional business models. Moreover, the emerging business models are able to take advantage of the affordances of the digitalisation of the economy to increase their geographic commercial reach, alter the manner of value creation and operate substantial business functions within a jurisdiction without the traditionally concomitant taxable or physical presence. Therefore, this dissertation evaluates and examines the adequacy of the existing South African framework for source-based taxation in its application to the new digitalised business models. Primarily, it is established that the ‘benefit theory' provides the theoretical justification for the imposition of tax on the basis of source, and therefore provides the normative framework through which the adequacy of the existing South African source rules is determined. Both the statutory rules and judicial approach to the determination of source are found to be inadequate in their application to the new digitalised business models. There is limited scope for the application of the existing statutory source rules, contained in s9 of the Income Tax Act, to the digitalised economy. The absence of a statutory rule for the determination of source with regard to digitalised business models places pressure on the judicial approach, which is ill-equipped to deal with the complexities of the digitalised economy. There exists limited scope to extend the judicial approach to determine the source of income in the absence of activity or physical presence on the part of the taxpayer. The introduction of statutory rules, as recommended by the Davis Tax Commission, has not yet materialised. The international project toward addressing the tax challenges of the digitalised economy provides some guidance in the formulation of a South African statutory response. The revenue sourcing rules – which determine the jurisdiction from which the revenue was derived – proposed by the Organisation for Economic Co-operation and Development and the African Tax Administration Forum provides for the identification of a sourcing principle for different streams of revenue, with a hierarchy of indicators to determine the source. This approach is advantageous in that it is cognisant that for different business models, different revenue souring rules are more appropriate and accurate. Alternatively, the approach adopted by the United Nation relies on the ‘payer principle', which is similar to the recommendation made by the Davis Tax Commission. However, the payer principle is criticised as it fails to allocate taxing rights to the place where the value was created.